Guidelines for exfoliation, characterization and processing of layered materials produced by liquid exfoliation - Backes, Claudia; Higgins, Thomas M. (Chemistry of materials, 2017)
Liquid phase exfoliation has become an important method for the production of large quantities of two-dimensional (2D) nanosheets. This method is versatile, having been used to produce dozens of different 2D materials in a range of stabilizing liquids. The resultant liquid-suspended nanosheets have been characterized in great detail and have been processed into a number of structures for a wide range of applications. This has led to a growing number of researchers adopting this method. As a result, best practice in terms of experimental procedure has evolved rapidly over recent years. As experimental complexity has increased, it has become more and more difficult to discuss the rational behind a chosen experimental procedure in full detail using standard “Methods” sections due to the frequent use of procedures developed in related prior reports. This can make it difficult to reproduce complex procedures and acts as a barrier to new researchers entering the field. To address this shortcoming, here we describe in detail the experimental methods and best practice used in our group when producing liquid exfoliated nanosheets.
Gesehen am 31.07.2018
Published online 2 November 2016